Immigration Aversion Under Labor Bargaining - Reksten, Nicholas; Rosete, Alfredo R. M. (Review of Economic Analysis, 2025)
The recent salience of immigration as an issue among segments of the population in wealthy countries has often been understood as a product of tension between economic interests and cultural preferences. However, such explanations largely ignore differences in power between immigrant and native communities and the cohesion of local community institutions. This article develops a bargaining model that highlights how power asymmetries between workers and employers interact with community cohesion to result in immigration aversion. Community cohesion among both migrant and native workers is modeled through their fallback positions. We show that the salience of immigration depends on the bargaining power of native and migrant workers. Further, we demonstrate that if the bargaining power of both native and migrant workers are low enough, then immigration aversion can exist even if immigration does not reduce labor demand for native workers.